CLINICAL AND EPIDEMIOLOGIC CONSIDERATIONS ON THE INTERACTION BETWEEN TEMPOROMANDIBULAR DISORDERS AND JUVENILE IDIOPATHIC ARTHRITIS - Cristina Brăileanu; Cristian Guțu; Monica Mihaela Scutariu; Iulia Olaru; Mădălina Duceac (Covrig); Georgeta Zegan (Romanian Journal of Oral Rehabilitation)
Temporomandibular disorders (TMD) are multisymptomatic conditions, with a frequency of 11-31% in the general population, that can lead over time to irreversible structural changes in the temporomandibular joint (TMJ). Juvenile idiopathic arthritis (JIA) is the most common inflammatory autoimmune disorder with joint involvement in childhood and is implicated in the genesis of temporomandibular dysfunction. Material and Methods. A prospective clinical-epidemiologic prospective study was carried out in the period 2022-2023 in the Children’s Emergency Clinical Hospital “Sf. Maria” in Iasi, with the aim of emphasizing the relationship between the two clinical entities. Results. Our research revealed some peculiarities of the relationship between JIA and TMD in a group of 156 children. Thus, JIA was more frequent in rural areas (53%), in females (66.66%), in the 8-11 (42.5%) and 12-16 (44.7%) age groups. TMD had a prevalence of 27%, also more frequent in females (64.3%) and in the 12-16 age group. The TMJ dysfunctional syndrome is plurimorphic, but in our study group the pain on loco-regional palpation, malocclusion, auricular and articular noises in the form of cracking and crackling attract attention. Conclusions. Our study emphasizes the relationship between juvenile idiopathic arthritis and temporomandibular joint disorders, stressing the need for interdisciplinary approach to TMJ pathology in childhood, with the input of specialists in the field of pediatric rheumatology, dentistry and individualized rehabilitation.